Bio-Medical CMOS ICs - Yoo, Hoi-Jun; van Hoof, Chris (Integrated Circuits and Systems,, 2011)
Bio-Medical CMOS ICs provides readers with the basic operation principles and architectures as well as the most recent research results of low power CMOS ICs especially for bio-medical applications. The book covers three parts:  Vital Signal Sensing and Processing from Neuronal Signal, Electrode and Readout IC, ADC to Bio-Signal Processor  Short Distance Bio-Medical Body Channel Communication and Wireless Communication  Examples of Attachable, Wearable and Implantable Bio-Medical IC and Its Applications Novel sensing, processing and communication methods are also introduced and analyzed, along with the basics of planning and designing healthcare systems that will shift healthcare paradigm from "reactive" illness management to "proactive and preemptive" health management. Bio-Medical CMOS ICs is a useful book for engineers, researchers and students in the field of CMOS technology.